The effect of metribuzin on the density of proteolytic microorganisms and proteolytic activity in different types of soil - Šantrić, Ljiljana R; Radivojević, Ljiljana; Sarić-Krsmanović, Marija; Gajić Umiljendić, Jelena; Đurović-Pejčev, Rada (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2018)
Soil texture and other physical and chemical characteristics of soil are important factors influencing the retention of herbicides in soil ecosystems. A laboratory experiment was conducted to estimate the response of proteolytic microorganisms to applications of metribuzin in different types of soil (loamy and sandy) in terms of density and protease activity. The following concentrations were tested: 12.0, 24.0, 120.0 and 1200.0 mg a.i.kg-1 soil. Samples were collected 7,14 and 30 days after treatment with metribuzin. Metribuzin did not affect the number of proteolytic microorganisms in loamy soil. In sandy soil, their number was reduced 26.7% by the highest concentration 7 days after application. Protease activity was reduced in both types of soil on the 7th and 14th day and the percentage of reduction was 21% for loamy soil and 29.9% for sandy soil. Statistical analysis of data showed that the correlation between test parameters was positive in both types of soil (r2=1 for loamy soil, and r2=0.81 for sandy soil). The study shows that metribuzin causes a passable impact on microbial population and enzymatic activity which depends on the type of soil.